(untitled) (JOURNAL OF ADVANCES IN PHYSICS, 2015)
Anthropogenic global warming (AGW) heat is trapped by the greenhouse gas (GHG) blanket, and the ocean surface layer. It is 93% in the ocean and drives atmospheric warming. The 111-year mean daily surface temperatures are 10.5±0.5°C at Port Erin (PE) Isle of Man compared with 9.6±4.8°C in Central England (CET) air. The Port Erin 5½-year max-min heat cycle synchronizes to the 11-year solar heat pump sunspot cycle. Tropical heat arrives 2 years after a solar maximum on wind-driven currents in the stratified sea surface. Runoff from bottom-up melted Arctic icesheets arrives 3½ year later at solar minimum. These warm and cold waters are the biodiversity source. PE is unique with seasonal meltwaters of Pacific and Atlantic origin. The North Pacific warms twice as fast as other oceans. All ocean near-surface gyre currents harmonize with sunspot cycles. Net cooling by polar icemelt masks catastrophic exponential ocean warming and icemelt. Eleven counter-rotating surface gyres carry heat and nutrients globally in verified ocean surface circulation system. Exponential growth is unsustainable in a finite system. It trends to infinity. Double-exponential gets there twice as quickly. The GHG blanket, grown double-exponentially for 250 years, is now in control. Ocean heat absorption takes 150-250years. Arctic icemelt increases double-exponentially. The Arctic long-term annual freeze-melt volume cycle is 16.8±1.3 thousand cubic km per year. Polar land icemelt adds 500 km3m per year. Freeze-brine of salinity >40‰ and temperature – 1°C, sinks to the bottom. Equatorial evaporative-brine of salinity >36.4‰ and >28°C floats subsurface under fresh warm layers thickening westwards in tropical meridional cells to 75m depth. This is consistent with observed extreme weather. Heat imbalance forced Pacific Ocean temperatures above proposed limits of +2°C in 1993, to +3°C in 2014, and is on track for +4°C for 2016. Century-long daily records confirm processes ongoing for 300 years. Coast locations are where impacts are felt and real-time data collected. Corporate governance degraded physics teaching in only 60 years. Individual discovery and data collection was lost. Big science is unnecessary. Satellites cannot do plankton tows. Computer modelsare governed by the rule of „garbage-in garbage-out?. They must be verified by in situ data that cannot be collected retrospectively. Continuous timeseries surface profile data from fixed ocean station locations on a global variableboundary network are essential. Scientists, if well-trained in ocean experimental physics, can do the hard work. Time-poor scientists, stripped of their intellectual property rights, under rewarded, poorly educated, and ruthlessly exploited by growth-obsessed commercial interests, missed catastrophic global warming and multiple extreme consequences. Climate scientists abandoned classical physics and Newton-Hooke field verification in favor of unverified beliefs, models, and apps. Climate studies confuse heat with temperature, do not include basal icemelt, density temperature-salinity function, Clausius-Clapeyron evaporation exponential skin temperature function, asymmetric brineheat sequestration, solar and tidal pumping, infra-red GHG heat trap, vertical tropical cells, freshwater warm pools; or wind-driven surface currents at 3 percent of windspeed. Climate model mistaken assumptions lead to the absurd conclusion that evaporation in the Labrador Sea at midnight in midwinter is greater than at the midday Equator. The Isle of Man provides an ideal location for continued monitoring and mitigation research, teaching and public service ina dedicated non-commercial independent multidisciplinary university-type setting. Quality teaching is the major priority. Commercial monopoly rights need replacement with free, fully open discussions and publications. Quality not quantity should be paramount. Internationally competitive academics should control subservient lower paid support staff. Every day without ocean surface data means vital scientific truth lost of interest and concern to all populations. Predictions are groundless without accurate continuous ocean surface data. Skeptics, politicians, statisticians, those with stakes in the status quo, and established research censors obstructing scientific progress squabble in ignorance while the globe burns.